Linguistic Study of Stance-Taking in Online Media - Sholikhah, I M (KnE Social Sciences, 2019)
This paper addresses stance-taking in an online media as nowadays people utilize them for several functions. Online media refers to communication technologies using the internet to present or exchange information. Online media used for several purposes such as selling products; advertising; sharing news, pictures, video, or information; or discussing such topics as politics, entertainment, education, and culinary. In achieving its goal, online media is systematically design. Every sentence has sort of persuasion, argumentation, and evaluation in an explicit way or implied to get better interaction with the readers. It needs the aspect of stance, which refers to lexical and grammatical expression of attitudes, feeling, judgments, or commitment cornering the proportional content of the message (Biber and Finegan in Myers: 2003,254). Stance is considered as important concept in linguistics which brings a wide range on how utterances’ meanings are expressed and how speakers (or writers) address their audience. Applying descriptive qualitative research, this paper is aimed at elicitting kinds of stance-taking utilized in google.com as one of the biggest online media. The researcher compiled the data by collecting the sentences which represent the act of stance taking then categorizing the kinds of stance-taking. The research resulted in finding that there are three kinds of stance: epistemic, attitudinal, and stylistic stance. Epistemic stance deals with the marking of certainty and uncertainty of the facts. Attitudinal stance concerns on personal perspective, aesthetic preference, as well as moral judgment or emotional response. Then, stylistic stance deals with the way of expressing idea. Keywords: discourse analysis, electronic discourse, website, stance taking